1967
DOI: 10.1177/002218566700900203
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Jobs

Abstract: JOB DESIGN means specification of the contents, methods, and relationships of jobs in order to satisfy technological and organizational requirements as well as the social and personal requirements of the job-holder.For the purposes of discussion only, specification of job contents can be divided into two categories: (1) physical-environment and physiological requirements, and (2) organization, social, and personal requirements. An extensive body of knowledge exists on the first category and is assiduously appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Herzberg (1966), Davis (1966), Davis and Valfer (1965,1966), and Emery, Thorsrud, and Lange (1966) represent the groups which have worked longest on horizontal and vertical job enlargement. All, together with Ford (1969), Sorcher (1967), and Paul, Robertson, and Herzberg (1969), have concluded that through the design of jobs that permit increased self-regulation, self-evaluation, self-adjustment, and participation to set goals, increases have been produced in productivity and positive attitudes.…”
Section: Job Enlargement or Enrichmentmentioning
confidence: 99%
“…Herzberg (1966), Davis (1966), Davis and Valfer (1965,1966), and Emery, Thorsrud, and Lange (1966) represent the groups which have worked longest on horizontal and vertical job enlargement. All, together with Ford (1969), Sorcher (1967), and Paul, Robertson, and Herzberg (1969), have concluded that through the design of jobs that permit increased self-regulation, self-evaluation, self-adjustment, and participation to set goals, increases have been produced in productivity and positive attitudes.…”
Section: Job Enlargement or Enrichmentmentioning
confidence: 99%
“…In these cases the introduction of office automation appeared to have improved the quality of the jobs themselves, on the basis of standard job design criteria [14]. There tended to be an accompanying increase in positive job attitudes, such as interest, involvement and enjoyment.…”
Section: Z -Decentralised Design With User Participationmentioning
confidence: 99%
“…In the occupational context, motivation is considered as the background to the interest in work design (Davis and Taylor, 1972), quality of working life (Davis and Cherns, 1975),job satisfaction (Sell and Shipley, 1979) and worker participation (Wall and Lischeron, 1977). Collectively these represent the 'job enrichment' movement which flourished in the sixties and early seventies when the western world was still in a period of full employment and there had been several decades of continuously increasing prosperity.…”
Section: Motivationmentioning
confidence: 99%